IMPLEMENTASI CORE VALUE PADA SISTEM KEY PERFORMANCE INDICATOR TERHADAP PENILAIAN KINERJA KARYAWAN PT. ARUNDATI APSHARA ABHIPRAYA - Adelina, Andi Rosita (Fakultas Pertanian, 2024)
A science or way of managing how the relationships and roles of resources owned by individuals are efficient and effective and can be used optimally to achieve common goals. Human Resource Management is the process of planning, organizing, directing and supervising human resources in a company to achieve an expected goal. One method of guiding and evaluating research efforts, encouraging accountability and improving the overall quality and impact of work is KPIs. Key Performance Indicators have an important role in providing a structured way to increase productivity in company or organizational performance management. KPI has core values that serve as standards for evaluating employee performance. There are core competencies and technical competencies. In the KPI assessment there are core values that form the basis for its implementation or Core values. Each division's core values have employee assessment standards depending on the company's goals. The purpose of writing this scientific work is to analyze the extent of the influence of the KPI system on human resource management.